PENGARUH PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS BERITA MAHASISWA PBSI FBS UNM - Muh. Ilham Ismail; Sulatriningsih Sulatriningsih; Sultan Sultan (Fakultas Teknik Universitas Negeri Makassar, 2023)
This study is a quantitative research with the aim to find out the significant influence between vocabulary mastery on news writing skills of Indonesian Language and Literature Education students, Faculty of Language and Literature, Makassar State University. The independent variable in this study is vocabulary mastery, while the dependent variable is news writing skills. The population in this study were 3 classes of Indonesian Language and Literature Education 2017 students totalling 102 people, while the sample was 72 students who had filled out the questionnaire. The research data were obtained by giving objective tests and work performance. The data analysis technique is by correlational analysis looking for the presence or absence of influence from the independent variable to the dependent variable. Based on the results of inferential statistical analysis of 0.455 with a significance level of 000. So there is a significant influence between vocabulary mastery on news writing skills. Vocabulary mastery supports students' skills in processing information into news.